Synchrotron radiation : basics, methods and applications - Mobilio, Settimio; Boscherini, Federico; Meneghini, Carlo (Springer Berlin Heidelberg Imprint: Springer, 2015)
Synchrotron radiation is today extensively used for fundamental and applied research in many different fields of science. Its exceptional characteristics in terms of intensity, brilliance, spectral range, time structure and now also coherence pushed many experimental techniques to previously un-reachable limits, enabling the performance of  experiments unbelievable only few years ago. The book gives an up-to-date overview of synchrotron radiation research today with a view to the future, starting from its generation and sources, its interaction with matter, illustrating the main experimental technique employed and provides an overview of the main fields of research in which new and innovative results are obtained. The book is addressed to PhD students and young researchers to provide both an introductory and a rather deep knowledge of the field. It will also be helpful to experienced researcher who want to approach the field in a professional way.